Brief of 172 Members of the U.S. House of Representatives and 40 U.S. Senators as Amici Curiae in Support of Respondent Edith Schlain Windsor, Urging Affirmance on the Merits - of the United States, The Supreme Court (Columbia Journal of Gender and Law, 2015)
Amici are 172 Members of the U.S. House of Representatives and 40 U.S. Senators.1 Some of us voted against the Defense of Marriage Act, Pub. L. No. 104-199, 110 Stat. 2419 (Sept. 21, 1996); others voted for it; still others were not yet in Congress when it was enacted. But we all agree that Section 3 of DOMA-which divides married couples into two classes and denies all federal responsibilities and rights to one of them-lacks a rational connection to any legitimate federal purpose, and is therefore un- constitutional. Members of Congress are bound by oath to sup- port and defend the Constitution. Thus, this Court’s interpretation of the Fifth Amendment’s equal-pro- tection guarantee directly affects how Congress drafts, considers, and enacts laws. We urge the Court to clarify that legislative classifications based on sexual orientation do not enjoy the presumption of validity appropriately afforded to most legislative acts. That guidance will help ensure that legislative classifications receive sufficient reflection. We also want to explain why, in this rare case, the Court should find an Act of Congress unconstitutional. Although we support legislative standing to de- fend legislation in appropriate cases, we disagree with the arguments made by the Bipartisan Legal Advisory Group in DOMA’s defense. Having repeat- edly urged Congress (including the Speaker of the House) to revisit DOMA legislatively, we believe it important to dispel the notion that BLAG speaks for the entire Congress on the merits. It does not. In fact, many Members believe that Section 3 of DOMA is a violation of the Fifth Amendment’s equal- protection guarantee and should be struck down.